KETIDAKPASTIAN HUKUM PENGAKUAN DAN PELAKSANAAN PUTUSAN ARBITRASE INTERNASIONAL DI INDONESIA : SYARAT KETERTIBAN UMUM - Napitupulu, Anton Anju; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: An International Arbitration Award can be recognized and enforced in Indonesia if it meets the conditions stipulated in Article 66 of Law Number 30 Year 1999 on Arbitration and Alternative Dispute Resolution, one of which includes the provision that the award is not contrary to public order. The problem with this requirement is that there is no definition or explanation of the public order provision, causing legal uncertainty and subjective interpretation among judges. The purpose of this study is to further analyze the legal uncertainty in the application of the principle of public order as a condition of recognition and enforcement of decisions of international arbitration bodies in Indonesia, as well as the impact on investment in Indonesia. It is hoped that this research can provide recommendations to make an improvement on the public order requirement. This is because the provision has been in effect for more than two decades and needs to be adjusted to the development of investment in the future to support the government's vision towards the Golden Indonesia Era.Keywords: Legal Uncertainty, International Arbitration Award, Public Order Principle.